2020
DOI: 10.1177/0284185120950115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of diffusion-weighted MRI for differentiation between benign and malignant gallbladder disease: a systematic review and meta-analysis

Abstract: Background Radiological differentiation between benign and malignant gallbladder disease is important but remains challenging. Furthermore, the clinical value of diffusion-weighted imaging (DWI) remains unclear. Purpose To determine the value of DWI in discriminating benign from malignant gallbladder disease by conducting a systematic review and meta-analysis. Material and Methods The literature was systematically searched. Studies analyzing diagnostic value of DWI in gallbladder disease with histopathology or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In addition, the results from a recent meta-analysis [20] further supported the role of MR-DWI to discriminate malignant from benign gallbladder lesions. In this article, the reported pooled sensitivity/specificity values were 0.87/0.84 across studies.…”
Section: Diffusion Mri To Discriminate Malignant and Benign Gallbladder Lesionsmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, the results from a recent meta-analysis [20] further supported the role of MR-DWI to discriminate malignant from benign gallbladder lesions. In this article, the reported pooled sensitivity/specificity values were 0.87/0.84 across studies.…”
Section: Diffusion Mri To Discriminate Malignant and Benign Gallbladder Lesionsmentioning
confidence: 82%
“…Future studies with a higher sample size may better evaluate the incidence of MR-DWI restriction within RAS and the degree of correlation between this radiological sign and histopathology-defined malignancies. In addition, future literature may further explore the differences in ADC measurements between benign and malignant gallbladder lesions in order to better validate the cutoff values of ADC proposed in the recent meta-analysis by Kuipers and colleagues [20].…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic accuracy for gallbladder carcinoma slightly improved after adding DWI to regular MRI, from 92% to 95% with overall statistical significance, indicating that DWI can improve diagnostic accuracy for gallbladder cancer [36]. Moreover, in a meta-analysis of 8 studies including a total number of 592 patients, performed by Kuipers et al in 2020, pooled sensitivity and specificity rates were found to be 0.87 and 0.84, respectively [37].…”
Section: Discussionmentioning
confidence: 94%
“…DWI has been widely used in cancer imaging to detect, characterize, and stage malignant lesions, or even assess the response to therapy, in various anatomical districts besides the brain [ 11 ], such as the breast [ 12 , 13 ], lung [ 14 , 15 ], liver [ 16 ], pancreas [ 17 ], kidney [ 18 ], gallbladder [ 19 ], thyroid [ 20 ], head and neck [ 21 , 22 ], prostate [ 23 , 24 ], vertebral bone marrow [ 25 ], musculoskeletal soft tissue [ 26 ], nasopharynx [ 27 ], ovaries [ 28 ], cervix [ 29 ], and rectum [ 30 ], as well as in the whole body [ 31 ].…”
mentioning
confidence: 99%